2004
DOI: 10.1074/jbc.m313002200
|View full text |Cite
|
Sign up to set email alerts
|

Structures of μO-conotoxins from Conus marmoreus

Abstract: The O-conotoxins are an intriguing class of conotoxins targeting various voltage-dependent sodium channels and molluscan calcium channels. In the current study, we have shown MrVIA and MrVIB to be the first known peptidic inhibitors of the transient tetrodotoxinresistant (TTX-R) Na ؉ current in rat dorsal root ganglion neurons, in addition to inhibiting tetrodotoxinsensitive Na ؉ currents. Human TTX-R sodium channels are a therapeutic target for indications such as pain, highlighting the importance of the O-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 51 publications
0
45
1
2
Order By: Relevance
“…The absence of Na v 1.4 in the CNS and the ability of MrVIB to inhibit only certain pain types after intraplantar injection argue against an involvement of Na v 1.4 in the reduction in pain behavior produced by MrVIB. The analgesic effect of MrVIB is also not expected to involve inhibition of voltage-gated calcium channels, because we have demonstrated that the isotoxin MrVIA is without effect on calcium currents in rat sensory neurons (14). The presence of normal neuropathic pain in Na v 1.8 or Na v 1.7͞Na v 1.8-knockout mice indicates that TTX-S channels (and other channels) are able to contribute to a greater or lesser extent to altered levels of neuronal excitability (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of Na v 1.4 in the CNS and the ability of MrVIB to inhibit only certain pain types after intraplantar injection argue against an involvement of Na v 1.4 in the reduction in pain behavior produced by MrVIB. The analgesic effect of MrVIB is also not expected to involve inhibition of voltage-gated calcium channels, because we have demonstrated that the isotoxin MrVIA is without effect on calcium currents in rat sensory neurons (14). The presence of normal neuropathic pain in Na v 1.8 or Na v 1.7͞Na v 1.8-knockout mice indicates that TTX-S channels (and other channels) are able to contribute to a greater or lesser extent to altered levels of neuronal excitability (30).…”
Section: Resultsmentioning
confidence: 99%
“…After screening crude venoms from Ϸ30 species, we identified two closely related conotoxins, O-conotoxin MrVIA and O-conotoxin MrVIB (MrVIB), which selectively inhibited the tetrodotoxin-resistant (TTX-R) sodium current without affecting calcium current in sensory neurons (14). Here, we determine the VGSC subtypeselectivity of MrVIB in rat sensory neurons and heterologous expression systems and establish its selectivity for pain pathways in rat models of persistent pain.…”
mentioning
confidence: 99%
“…Spectra were recorded at 290 K on a Bruker AVANCE-600 spectrometer. Two-dimensional NMR spectra were recorded in phase-sensitive mode using time-proportional phase incrementation for quadrature detection in the t1 dimension (19,20). The two-dimensional experiments consisted of a TOCSY using a MLEV-17 spin lock sequence with a mixing time of 80 ms, DQF-COSY, and NOESY with mixing times of 200 -300 ms. Solvent suppression was achieved using a modified WATERGATE sequence.…”
Section: Materials-t-butoxycarbonylmentioning
confidence: 99%
“…The starting structures were generated using random ( , ) dihedral angles and energy-minimized to produce structures with the correct local geometry. A set of 50 structures was generated by a torsion angle simulated annealing protocol (19,20). This protocol involved a high temperature phase comprising 4000 steps of 0.015 ps of torsion angle dynamics, a cooling phase with 4000 steps of 0.015 ps of torsion angle dynamics during which the temperature was lowered to 0 K, and finally an energy minimization phase comprising 500 steps of Powell minimization.…”
Section: Materials-t-butoxycarbonylmentioning
confidence: 99%
“…mО-Конотоксины mО-MrVIA и mО-MrVIB способны ингибировать потенциалзависимые натриевые каналы нейронов моллюсков, амфибий [66] и млекопитающих [44,[66][67][68][69][70]. Эти токсины ингибируют ТТХ-устойчивые натриевые каналы Nav.8 нейронов крысы значительно эффективнее, чем ТТХ-чувствительные [67,68].…”
Section: Mо-конотоксины и D-конотоксиныunclassified